XILANASE EM DIETAS PARA AVES: REVISÃO SISTEMÁTICA - Gislaine da Cunha de Andrade (2023)
The use of exogenous enzymes has become indispensable over the years in diets for non-ruminants. A study was conducted with the objective of evaluating the techno-economic performance of broilers fed diets supplemented with xylanase through a systematic review. Peer-reviewed publications were included in this review through the online database platform Google Scholar. The searches were conducted between the months of January 2021 to January 2023, and studies involving the use of commercial xylanases from 2011 onwards were selected with the keywords used "xylanase", "broilers" for the searches. The secondary eligibility criteria were: performance studies with at least 40 days, with three diets (formulation according to nutritional requirements without xylanase, energy-reduced diet without xylanase and energy-reduced diet containing xylanase), the online database contained about 10,390 publications. Once the publications were checked, eight articles were selected, with a total of 11,761 animals used, enzyme activity ranging from 12,000 to 24,000 BXU and energy reductions ranging from 50 to 150 Kcal ME/kg. Performance data were evaluated and these were submitted to an economic evaluation at the end of the analyses. The results show that, diets with energy reduction with inclusion of xylanase present cost per ton, cost, revenue, profit and gross margin higher than the basal diet and the diet with energy reduction. The standard and pessimistic scenarios show that diets with xylanase are more profitable than the others, even with four times higher values of the enzyme on the market. The performance variables were higher for the basal diet compared to the energy-reduced diet and energy-reduced diet with xylanase. Although there is economic efficiency on the part of diets with xylanase inclusion and energy reduction, providing a lower nutritional cost in relation to basal diet and energy reduction diet. The inclusion of xylanase in diets with energy reduction for broilers provides lower results than basal diet and higher results thanenergy reduction diet. Keywords: additives, antinutritional factors, aviculture, carbohydrases, costs, performance